Modern Prospects for the Application of Mechatronics and Robotics Capabilities - Aliyev, Aydin; Yalchinkaya, Abdulkadir (Journal of Ecohumanism, 2024)
This article explores the application of mechatronics and robotics capabilities. In recent years a new quickly developing scientific and technical activity was created. It is called Mechatronics and represents an innovative field of science and equipment where the high-precision mechanics connects to the same exact electronics under control of the most modern computer programs [1],[2]. As a result difficult mechanisms of computer motion control with tremendous functionality are created. Industrial robots are striking examples of such mechanisms. Besides, there are mechanisms of retracting plane flaps and the chassis, many systems of a modern car and "smart houses". Technical and technological progress is impossible without mechatronics [3],[4]. Robotics and industrial automatic equipment in various branches of economy, automation of technological processes, systems of planning and business management, automation of transport, dispatching and other systems falls within the scope of its interests. Nowadays “Mechatronics” is one of the most demanded educational majors in the world. Mechatronics specialists are demanded in different areas: in power engineering, machine-tool design and production of the equipment, automation of technological processes, robotics and automotive industry. Security systems, military equipment, the medical equipment can't be designed without mechatronics.